ChemInform Abstract: KI/TBHP‐Mediated Oxidative Cross‐Coupling of Enamines and Carboxylic Acids under Metal‐Free Conditions: A Facile Access to Functionalized 2H‐Azirines. Issue 29 (June 2016) - Duan, Xiyan; et al.,
Abstract: A novel method for the synthesis of the acyloxylated 2H‐azirines through oxidative cross coupling reaction between the enamines and acids in MeCN is described.